The safety, efficacy, and influencing factors of biodegradable versus metallic occluders in the treatment of migraine patients with patent foramen ovale - Sun, Ke; Yang, Chenyu; Zhou, Tian; Zhou, Qing; Tian, Junchao; Sheng, Bo; Wang, Yunfei; Zhu, Xuetao; Hu, Zeping (Frontiers in Neurology, 2025)
ObjectiveCompare the efficacy and safety of biodegradable versus metallic occluders in the treatment of migraine patients with patent foramen ovale (PFO), and analyze the predictive factors for migraine attack relief.MethodA single-center retrospective study included 133 patients diagnosed with migraine with PFO in Hefei High-Tech Cardiovascular Hospital from January 2021 to June 2024; 56 cases were treated with biodegradable occluders, and 77 cases were treated with metallic occluders. Collect preoperative baseline data, use the Migraine Disability Assessment (MIDAS) Questionnaire and monthly attack days to assess symptoms, and evaluate efficacy at 1-year follow-up after surgery. Effectiveness is defined as complete elimination of migraine symptoms or a reduction of ≥ 50% in monthly attack days.ResultsThe postoperative MIDAS score (biodegradable group: 10.45 ± 9.19 vs. metallic group: 11.32 ± 9.62, p = 0.453) and the number of migraine attacks per month (biodegradable group: 2.09 ± 1.58 days vs. metallic group: 1.87 ± 1.43 days, p = 0.506) after surgery showed no statistically significant differences in both groups. The MIDAS scores and the number of migraine attacks per month both demonstrated statistically significant differences between the preoperative and postoperative periods in each group (p < 0.05). No significant complications occurred during the perioperative period. The number of mild adverse events was limited and could not be statistically analyzed. Multivariate analysis showed that preoperative MIDAS scores, the number of migraine attacks per month, right-to-left shunts (RLS) at rest, and Platelet Crit (PCT) were the same independent predictors of postoperative remission for both types of occluders; in addition, C-reactive protein (CRP) is only an independent predictor of remission in the metallic occluder group.ConclusionPFO closure can markedly alleviate symptoms in migraine patients with PFO. Both biodegradable and metallic occluders exhibit comparable efficacy in symptom improvement and safety at the 12-month postoperative mark. Patients presenting with more severe baseline migraine, RLS at rest, and elevated PCT may derive greater benefit from PFO closure, whereas lower CRP levels may portend a more favorable prognosis for those with metallic occluders. Biodegradable occluders may become a better choice for specific populations (such as young patients and those allergic to nickel).